PENAMBAHAN GIBERALIN (GA3) DAN SUHU DINGIN TERHADAP MASA SIMPAN BUNGA GLADIOL DALAM KEMASAN PLASTIK - Longdong, Ireine A.; Lengkey, Lady; Kairupan, Stella (Universitas Sam Ratulangi, 2011)
ABSTRACT This study aimed to obtain the concentration and duration of immersion Giberalin type GA 3 the most effective way to extend the shelf life of gladiolus flowers, and to get the type of packaging and the right temperature in prolonging the shelf life of gladiolus flowers to prolong shelf life. Descriptive method was used in two experiments. The first experiment was GA3 concentration and immersion time on the shelf life of gladiolus flowers. The second experiment was the type of packaging and cold temperatures on the shelf life of gladiolus flowers. The result of first experiment showed that gladiolus flowers soaked at a concentration of 250 ppm GA3 and 1 hour immersion time gives had the lowest value. CO2 production was ranged from mlCO2/kg.hours 18:43 to 33.30 mlCO2/kg.hours. Severe shrinkage rates in day two ,four and six were 27.92%, 36.31% and 40.27% respectively. The degree of gladiolus flowers bloom in the day two was 42.85% and degree of on day four was 33.63%. The results of second experiment showed that gladiolus flowers packed in polypropylene plastic storage temperature of 50C for 12 days resulted the lowest value. CO2 production were ranged from 8.68 mlCO2/kg.hours - 15:10 mlCO2/kg.hours. The severe shrinkage in first day was 1 27.29%. The degree of blooming in the 8 th day was 9.63%. Degree of wilting during 12 days storage was 0%. Keywords: Flowers gladiolus, Giberalin, cold temperatures, shelf life, plastic packaging